4-Chloro-2-(2-chlorobenzoyl)phenol - A. Bushra Begum; S. Madan Kumar; B. C. Manjunath; Shaukath Ara Khanum; N. K. Lokanath (Acta Crystallographica Section E, 2013)
In the title molecule, C13H8Cl2O2, the dihedral angle between the benzene rings is 74.53 (9)°. An intramolecular O—H...O hydrogen bond leading to a S(6) ring is observed. In the crystal, the molecules are connected into a three-dimensional network by C—H...O and π–π [inter-centroid distance = 3.6254 (10) Å] interactions.